Jordanian State Universities Developmental Centers for Building the Competences of the Academic and Administrative University Teaching Staff - Omar Rababah (Ali Khorsandi Taskoh, 2023)
The study aimed to evaluate the role of the performance development centers for teaching staff members at Jordanian state universities to develop academic and administrative capabilities. The descriptive approach was used to investigate and achieve the study's objectives. The study sample comprised six hundred teaching staff and adopted a twenty-nine-item questionnaire. The study results showed that the evaluation of the role of teaching staff at development centers in the Jordanian state universities in building academic and administrative capacities is of a high degree. Some results showed a set of suggestions from teaching staff members to improve the role of the centers. The study recommended that the university administration implement the suggestions of faculty members to increase the teaching process's effectiveness. Also, higher education institutes worldwide can see their suggestions and apply what is necessary in their institutes.